PENGEMBANGAN MODUL MENULIS CERPEN BERBANTUAN PETA PIKIRAN UNTUK PEMBELAJARAN MENULIS CERPEN KELAS X SMA - Nidde Puspita (Ensiklopedia of Journal, 2019)
The of conducting a research and development (R&D) originated from the lack SMA Negeri 2 Kerinci and SMA Negeri 4 Kerinci student’ knowledge and skills of writing short stories. The inabilities of writing short stories were first caused by the insufficient support of Indonesia instructionalresoursces and materials. The second was the lack of Indonesia teachers’ creativity in teaching the materials of writing short stories. The third is the lack of the students’ creativity in learning. The instructional systems design used in this research was 4D (Define,Design, Develop, and Disseminate). The qualitative data obtain from interviews meanwhile quantitative data were from the expert validation, Indonesian teachers, students and students’ learning outcomes. In conclusion, firstly, the module validity of writing short stories based mind mapping is valid. The percentage of its validity is 83,67%. Secondly, the practicality of the product developed is highly practical with the percentage of 89,70% by SMA 2 Kerinci the Indonesian teachers, the percentage of 91,18% by SMA 4 Kerinci the Indonesian teachers, 81,32% by SMA 2 Kerinci students and 79,69% by SMA 4 Kerinci students. Thirdly, the effectiveness of a module of writing short stories is highly effective with the percentage of 92,66% SMA 2 Kerinci and 92,33% SMA 4 Kerinci. 30 students from SMA 2 Kerinci scored 90,00% and 30 students from SMA 4 Kerinci scored 90,00% which highly assumed that this achievement has exceeded KKM. Therefore, this module can be made uses of as Indonesian instructional material, particularly for material of writing short stories.